(untitled) (Repertorio Científico, 2022)
The mismanagement of the stubble in pineapple cultivation together with the decomposition process of the same, favors the proliferation of the stable fly (Stomoxys calcitrans), since it serves as a means to oviposit their eggs in these stubble and thus complete their cycle biological, in addition the fly attacks the cattle of nearby farms generating economic losses. The parasitoid wasp Spalangia endius is a biological controller that has been reported as efficient for the control of the stable fly, this genus of parasitoids exhibits a wide distribution in the American Continent, its presence has been reported from the United States to Uruguay. These parasitoids usually deposit an egg in the pupa of the fly after having pierced the pupal envelope (puparium) with the ovipositor, the parasitoid egg develops through three larval stages at the same time that it feeds on the fly’s pupa and destroys it. The parasitoid pupates inside the fly’s puparium and then makes a hole to emerge, emerging another parasitoid. Due to the above and the potential of S. endius as a biocontroller, a massive rearing method was carried out with an alternate host at the pupal level and later, the parasitoid wasp was released in the field under variable ratios of female:pupae and under two depths of pupal laying in order to observe the behavior of the wasp and evaluate its potential as a biological control method.An artificial breeding test of S.endius was carried out on pupae of Ceratitis capitata as an alternate host and under laboratory conditions. In entomological cages the pupae were exposed to the wasp for 4 weeks to increase the brood stock. On the other hand, at the field level, artificial cages were built, cotton with a 10% sugar solution was added to feed the adults, females were released in proportions 1:10, 1:15 and 1:20 (female: pupae) as treatments and S.calcitrans pupae were intentionally placed at 5 and 15 cm depth to view oviposition and parasitism under two laying depths.Regarding the results obtained in the laboratory, an increased percentage of parasitism was recorded as the weeks of exposure passed, going from 12.8% to 69.0% in the last week of exposure. For its part, in the release of the parasitoid in the field under the cage method, it was obtained that, the best female:pupae ratio was 1:10 regardless of depth (p <0.05), an average of 94.4% of parasitism was reached with this dose. On the other hand, analyzing the oviposition depth there were no significant differences (p> 0.05), the female oviposits both at 5 cm and at 15 cm, for which it is concluded that the parasitoid has a penetration capacity in the stubble. A natural mortality of the pest of 50% was identified, so it is recommended to take this factor into account when conducting field monitoring and making control decisions. It is concluded that the parasitoid is a successful biological control alternative to implement in Costa Rica, since pineapple is one of the most important crops for the country and in which there has been an impact on the environment and livestock activity.